False‐positive 123I‐metaiodobenzylguanidine scan in a patient with renal cell carcinoma: A case of chromophobe renal cell carcinoma oncocytic variant with a complicated clinical course. Issue 1 (24th October 2020) - Suyama, Takahito; Kanesaka, Manato; Fujimoto, Ayumi; Otsuka, Kotaro; Hou, Kyokushin; Araki, Kazuhiro; Masuda, Hiroshi; Kojima, Satoko; Yamazaki, Kazuto; Naya, Yukio
Abstract : Introduction: 123 I‐metaiodobenzylguanidine scanning has high sensitivity and specificity for the diagnosis of tumors derived from sympathetic nerves or the adrenal medulla. We report the rare case of a 123 I‐metaiodobenzylguanidine false‐positive renal cell carcinoma. Case presentation: The patient was referred to our hospital with an incidental left renal mass during evaluation for hypertension. An ovarian tumor and prominent ascites were also observed. Serum and urine catecholamine levels were high to suspect a catecholamine‐producing tumor of the kidney. 123 I‐metaiodobenzylguanidine scintigraphy showed increased 123 I‐metaiodobenzylguanidine intake in the tumor. Laparoscopic radical left nephrectomy was performed. The pathologic diagnosis was an oncocytic variant of chromophobe renal cell carcinoma. No pheochromocytoma features were found. Conclusion: We report the first case of a 123 I‐metaiodobenzylguanidine false‐positive renal cell carcinoma. This case was diagnosed with primary aldosteronism and Meigs' syndrome, which made the clinical course more complicated.